Cathode material precursor, preparation method thereof, cathode material, battery and electrical equipment
Patent Information
- Application Number
- CN202611339940.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-09
AI Technical Summary
目前,现有镍锰氢氧化物前驱体烧制得到的正极材料,在高电压下难以兼顾倍率性能和循环性能的高性能需求
[0004]本申请提供一种正极材料前驱体及其制备方法、正极材料、电池和涉电设备,旨在解决上述的问题或者至少缓解上述现有技术中所存在的缺陷。
Smart Images

Figure CN122877831A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of lithium battery technology, and particularly relates to a cathode material precursor and its preparation method, cathode material, battery and electrical equipment. Background Technology
[0002] Nickel-manganese hydroxide (NMH) as a precursor for cathode materials offers advantages such as low cost and high energy density, with a watt-hour cost comparable to lithium iron phosphate (LFP). However, cathode materials prepared from existing NMH precursors struggle to simultaneously meet the high-performance requirements of rate capability and cycle life under high voltage.
[0003] In view of the above, this application is hereby submitted. Summary of the Invention
[0004] This application provides a cathode material precursor and its preparation method, a cathode material, a battery, and an electrical device, aiming to solve the above-mentioned problems or at least alleviate the defects existing in the prior art.
[0005] The first aspect of this application provides a cathode material precursor, which is a hydroxide containing the metal elements Ni, Mn, and Al. The molar amount of Mn accounts for more than 0.5% of the total molar amount of the cathode material precursor, and the molar amount of Al accounts for 0.010-0.147% of the total molar amount of the cathode material precursor. The average particle size D50 of the cathode material precursor is 3μm-6μm. The tap density TD of the cathode material precursor satisfies the following relationship: TD=k×φ -0.393 The unit of TD is g / cm³. 3 k is 0.6229 g / cm³ 3 -0.9526g / cm 3 φ is the mass fraction of Al in the cathode material precursor × 100.
[0006] The cathode material precursor of this application is a high-manganese, high-aluminum, small-particle-size nickel-manganese hydroxide. After sintering, it exhibits a spinel structure and possesses high voltage advantage. In particular, the tap density TD of the cathode material precursor satisfies the following relationship: TD = k × φ -0.393 This means that the small-particle-size cathode material precursor still maintains a high tap density even with high aluminum doping. Its secondary particles have a denser internal crystal structure and a larger contact surface between primary particles, which optimizes the ion transport path. Moreover, after being made into cathode material, this structure can effectively suppress particle pulverization under high voltage, thus taking into account both excellent rate performance under high voltage and long cycle stability.
[0007] In some embodiments, the relative standard deviation (RSD) of the mass content distribution of Al element in the cathode material precursor is less than 20%; alternatively, the relative standard deviation (RSD) of the mass content distribution of Al element is less than 10%.
[0008] In some implementations, the cathode material precursor satisfies at least one of the following conditions: A. The mass fraction of Al in the cathode material precursor is 0.1wt%-5wt%; B. The tap density (TD) of the cathode material precursor is 0.5 g / cm³. 3 -1.8 g / cm 3 ; C. The specific surface area (BET) of the cathode material precursor is 15 m². 2 / g -40 m 2 / g; D. The particle size distribution K90 of the cathode material precursor is 0.6-1.0; The molar amounts of E and Ni account for 0.10-0.25% of the total molar amounts of metals in the cathode material precursor; optionally, the molar amounts of Ni account for 0.15-0.25% of the total molar amounts of metals in the cathode material precursor; optionally, the molar amounts of Ni account for 0.20-0.25% of the total molar amounts of metals in the cathode material precursor. The molar amounts of F and Mn elements account for 0.70-0.80% of the total molar amounts of metals in the cathode material precursor; G. The cathode material precursor also contains the metallic element Co, and the molar amount of Co accounts for less than 0.05% of the total molar amount of metal in the cathode material precursor.
[0009] In some implementations, the chemical formula of the cathode material precursor is: Ni x Co y Mn z Al a T b (OH) 2+δ , Wherein, 0.10≤x≤0.25, 0≤y≤0.05, 0.70≤z≤0.80, 0.010≤a≤0.147, 0≤b≤0.01, 0.01≤δ≤0.19, x+y+z+a+b=1, and the doped metal element T is at least one of W, Y, Mo, Nb, Zr, Ti, and Sb.
[0010] A second aspect of this application provides a method for preparing the cathode material precursor as described above, comprising: A co-precipitation reaction is carried out by passing a metal salt solution containing Ni, Mn and Al elements, a complexing agent solution and a precipitant solution into a bottom liquid containing a precipitant and a complexing agent to obtain a hydroxide slurry with the target particle size. The hydroxide slurry was post-processed to obtain the cathode material precursor.
[0011] In some embodiments, the preparation method satisfies at least one of the following conditions: (1) The metal salt of the metal salt solution includes one or more of sulfate, nitrate or chloride salts containing Ni, Mn or Al elements; optionally, the metal salt of the metal salt solution also includes one or more of sulfate, nitrate or chloride salts doped with metal element T. (2) The precipitant includes one or more of sodium carbonate, sodium hydroxide, or potassium hydroxide; (3) Complexing agents include one or more of ammonia, oxalic acid, and ethylenediaminetetraacetic acid; (4) The total mass concentration of metal salts in the metal salt solution is 100 g / L - 150 g / L; (5) The mass fraction of the solute in the precipitant solution is 30wt%-70wt%; (6) The mass fraction of the solute in the complexing agent solution is 10wt%-30wt%; (7) The pH of the base solution is 10.5-12.0; (8) The concentration of the complexing agent in the base liquid is 1.5 g / L-3 g / L.
[0012] In some embodiments, the preparation method satisfies at least one of the following conditions: (9) The coprecipitation reaction is carried out under stirring at a speed of 300 rpm to 900 rpm; (10) During the coprecipitation reaction, the flow rate of the metal salt solution is controlled to be 1% / h - 15% / h of the reaction vessel volume; (11) Control the pH value during the coprecipitation reaction to decrease from 10.5-12.0 to 9.0-10.0; (12) Control the concentration of the complexing agent during the coprecipitation reaction to decrease from 1.5 g / L-3 g / L to <1.5 g / L; (13) During the coprecipitation reaction, the mother liquor is discharged through the concentration equipment, and the discharge rate of the mother liquor is consistent with the total inflow rate; (14) Post-processing includes dehydration, washing and drying processes performed sequentially.
[0013] The third aspect of this application provides a cathode material, which is prepared by calcining lithium-ion cathode material precursors obtained by the cathode material precursor preparation method described above.
[0014] The fourth aspect of this application provides a battery, wherein the positive electrode of the battery is made of the aforementioned positive electrode material.
[0015] The fifth aspect of this application provides an electrical device, including the battery as described above.
[0016] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description
[0017] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0018] Figure 1 The image shows the surface morphology of the secondary particles of the cathode material precursor prepared in Example 1 using SEM. Detailed Implementation
[0019] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0020] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0021] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0022] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0023] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0024] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0025] To address the problem that existing nickel-manganese hydroxide precursors struggle to balance rate performance and cycle performance under high voltage, this application provides a cathode material precursor. The cathode material precursor is a hydroxide containing the metal elements Ni, Mn, and Al. The molar amount of Mn accounts for more than 0.5% of the total molar amount of the cathode material precursor, and the molar amount of Al accounts for 0.010-0.147% of the total molar amount of the cathode material precursor. The average particle size D50 of the cathode material precursor is 3μm-6μm. The tap density TD of the cathode material precursor satisfies the following relationship: TD=k×φ -0.393 Where k is 0.6229 g / cm³ 3 -0.9526g / cm 3 φ is the mass fraction of Al in the cathode material precursor × 100.
[0026] It is understood that the cathode material precursor in the embodiments of this application can be a nickel-manganese hydroxide with high manganese, high aluminum doping, and small particle size. The molar amount of Mn element accounts for more than 0.5% of the total molar amount of metal in the cathode material precursor. Correspondingly, the molar amount of Ni element accounts for less than 0.5% of the total molar amount of metal in the cathode material precursor, forming a high manganese and low nickel composition. After being mixed with lithium and sintered into cathode material, it has a spinel structure. The cathode material has a high lithium-ion migration rate and has a high voltage advantage.
[0027] Furthermore, the molar amount of Al in the cathode material precursor accounts for 0.010-0.147 of the total molar amount of metal in the cathode material precursor. The cathode material precursor has a high Al doping amount. On the one hand, Al can replace some Ni and Mn elements, reducing the cost of raw materials. On the other hand, appropriate Al doping stabilizes the spinel structure of the cathode material, suppresses phase transition and Mn dissolution under high voltage, so as to effectively balance cycle performance and rate performance.
[0028] Furthermore, an average particle size D50 of 3μm-6μm for the cathode material precursor is beneficial for balancing rate performance and cycle stability under high voltage. If the average particle size D50 is too small, the specific surface area of the cathode material precursor will be too large, which will intensify the side reactions on the cathode material surface after sintering and worsen the cycle performance. If the average particle size D50 is too large, the lithium-ion diffusion path of the cathode material will be too long, which is not conducive to improving rate performance.
[0029] Based on this, the tap density of the cathode material precursor in the embodiments of this application satisfies the following relationship: TD=k×φ -0.393 Where k is 0.6229 g / cm³ 3 -0.9526g / cm 3 φ is the mass fraction of Al in the cathode material precursor × 100.
[0030] The formula for calculating φ above is: m 正极材料前驱体 This refers to the mass of the cathode material precursor sample. m Al This represents the mass of Al in the cathode material precursor sample.
[0031] For example, calculate whether the tap density TD (test value) of the cathode material precursor in Example 1 satisfies the relationship: TD=k×φ -0.393 : Given that the mass fraction of Al is 0.30%, then φ is 0.30. When k = 0.6229 g / cm 3 When this is the case, the lower limit for calculating TD is approximately 1.00 g / cm³. 3 , When k = 0.9526 g / cm 3 When the upper limit of TD is calculated, it is approximately 1.53 g / cm³. 3 , The actual measured TD was 1.26 g / cm³. 3 The calculation ranges from the upper limit of TD to the lower limit of TD, which is 1.00 g / cm³. 3 -1.53g / cm 3Within the specified range, that is, the tap density TD (test value) of the cathode material precursor in Example 1 satisfies the following relationship: TD = k × φ -0.393 .
[0032] When the coefficient k is 0.6229 g / cm³ 3 -0.9526g / cm 3 Under the condition that the Al content and tap density (TD) have a power function relationship, the TD decreases more slowly as the mass fraction of Al in the cathode material precursor increases. This is achieved by maintaining the k value at 0.6229 g / cm³. 3 -0.9526g / cm 3 Within the specified range, under the dual constraints of high aluminum doping and small particle size, the cathode material precursor of this application embodiment can maintain a high tap density TD, thereby ensuring the compaction density and volumetric energy density of the cathode material after sintering. The secondary particles of the cathode material have a dense internal crystal structure and a large contact surface of the primary particles, which is conducive to the optimization of ion transport paths and suppresses particle pulverization under high voltage, so as to achieve both excellent rate performance and long cycle stability under high voltage.
[0033] It should be noted that, in the embodiments of this application, the cathode material precursor is a hydroxide containing Ni, Mn, and Al elements, wherein the molar amount of Mn element accounts for more than 0.5% of the total molar amount of metal in the cathode material precursor. For example, the molar amount of Mn element in the total molar amount of metal in the cathode material precursor can be 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, or 0.6... 7. Any value within the range of 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.95 or 0.50-0.85, 0.50-0.60, 0.60-0.70, 0.70-0.80, 0.80-0.90, 0.55-0.75, 0.65-0.80, or above 0.5. Accordingly, the molar amount of Ni in the cathode material precursor is less than 0.5% of the total molar amount of metal. For example, the molar amount of Ni in the cathode material precursor can be any value within the range of 0.01, 0.10, 0.12, 0.15, 0.18, 0.20, 0.22, 0.24, 0.25, 0.30, 0.32, 0.35, 0.38, 0.40, 0.42, 0.44, 0.45, 0.48, 0.5, or 0.01-0.10, 0.10-0.20, 0.20-0.30, 0.30-0.40, 0.40-0.50, 0.05-0.25, 0.15-0.25, 0.20-0.35, or 0.01-0.5. The molar amount of Al element accounts for 0.010-0.147 of the total molar amount of metal in the cathode material precursor. For example, the molar amount of Al element can be any value within the range of 0.010, 0.020, 0.030, 0.040, 0.050, 0.060, 0.070, 0.080, 0.090, 0.100, 0.110, 0.120, 0.130, 0.140, 0.147 or 0.010-0.147.
[0034] In this embodiment of the application, the average particle size D50 of the cathode material precursor is 3μm-6μm. Exemplarily, D50 can be any value within the range of 3.0μm, 3.25μm, 3.5μm, 3.75μm, 4.0μm, 4.25μm, 4.5μm, 4.75μm, 5.0μm, 5.25μm, 5.5μm, 5.75μm, 6.0μm or 3μm-6μm.
[0035] In this embodiment, the tap density TD of the cathode material precursor satisfies the following relationship: TD=k×φ -0.393 Where k is 0.6229 g / cm³ 3 -0.9526 g / cm 3 For example, k can be 0.6229 g / cm³. 3 0.6250g / cm 3 0.6300g / cm 3 0.6350g / cm 3 0.6400g / cm 3 0.6450g / cm 3 0.6500g / cm 3 0.6550g / cm 3 0.6600g / cm 3 0.6650 g / cm 3 0.6700g / cm 3 0.6750 g / cm 3 0.6800g / cm 3 0.6850 g / cm 3 0.6900g / cm 3 0.6950 g / cm 3 0.7000g / cm 3 0.7050g / cm 3 0.7150g / cm 3 0.7200g / cm 3 0.7250g / cm 3 0.7300g / cm 3 0.7350g / cm 3 0.7400g / cm 3 0.7450g / cm 3 0.7500g / cm 3 0.7550g / cm 3 0.7600g / cm 3 0.7650 g / cm 3 0.7700g / cm 30.7750 g / cm 3 0.7800g / cm 3 0.7850 g / cm 3 0.7900g / cm 3 0.7950 g / cm 3 0.8000g / cm 3 0.8050 g / cm 3 0.8150g / cm 3 0.8200g / cm 3 0.8250g / cm 3 0.8300g / cm 3 0.8350g / cm 3 0.8400g / cm 3 0.8450 g / cm 3 0.8500g / cm 3 0.8550g / cm 3 0.8600g / cm 3 0.8650 g / cm 3 0.8700g / cm 3 0.8750 g / cm 3 0.8800g / cm 3 0.8850 g / cm 3 0.8900g / cm 3 0.8950 g / cm 3 0.9000g / cm 3 0.9050g / cm 3 0.9150g / cm 3 0.9200g / cm 3 0.9250g / cm 3 0.9300g / cm 3 0.9350g / cm 3 0.9400g / cm 3 0.9450g / cm 3 0.9500g / cm 3 0.9526 g / cm 3 Or 0.6229 g / cm 3 -0.9526g / cm 3 Any value within the range.
[0036] In some embodiments, the relative standard deviation (RSD) of the mass content distribution of Al element in the cathode material precursor is less than 20%; alternatively, the relative standard deviation (RSD) of the mass content distribution of Al element is less than 10%.
[0037] It should be noted that the relative standard deviation (RSD) is the ratio of the standard deviation to the arithmetic mean, and the formula is as follows: In the formula, RSD is the relative standard deviation of the mass content distribution of Al element; SD is the standard deviation of the mass content distribution of Al element; This represents the average mass content of Al element; N is the number of samples containing the mass content of Al element; i is the sample number, i = 1, 2, ..., N; xi is the mass content detection value of the i-th Al element.
[0038] A smaller RSD indicates a more uniform distribution of Al elements in the cathode material precursor. In the embodiments of this application, the relative standard deviation (RSD) of the mass content distribution of Al elements is less than 20%, which means that the Al elements in the cathode material precursor are uniformly distributed, making ion / electron transport more consistent, suppressing local structural distortion and stress concentration, stabilizing the crystal lattice framework, reducing harmful phase transitions, and lowering local polarization, thus facilitating further improvement in cycle performance.
[0039] In the cathode material precursor, the relative standard deviation (RSD) of the Al element mass content distribution is less than 20%. For example, the RSD of the Al element mass content distribution can be any value or range of 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, <20%, <19%, <18%, <17%, <16%, <15%, <14%, <13%, <12%, <11%, <10%, <9%, <8%, <7%, <6%, <5%, <4%, <3%, <2%, or <1%.
[0040] In some embodiments, the relative standard deviation (RSD) of the Al mass content distribution is less than 10%, resulting in a more uniform Al mass content distribution in the product and further improving cycle performance.
[0041] In some embodiments, the mass fraction of Al in the cathode material precursor is 0.1wt%-5wt%. For example, the mass fraction of Al in the cathode material precursor can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2.0wt%, 2.1wt%, 2.2wt%, 2 The Al content in the cathode material precursor can be any value within the range of 0.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3.0wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.5wt%, 3.6wt%, 3.7wt%, 3.8wt%, 3.9wt%, 4.0wt%, 4.1wt%, 4.2wt%, 4.3wt%, 4.4wt%, 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt%, 5.0wt%, or 0.1wt%-5wt%. If the Al content in the cathode material precursor is too low, the cycle improvement effect is not significant; while if the Al content is too high, it may lead to increased structural distortion and a rapid decrease in tap density. A mass fraction of Al in the cathode material precursor within the range of 0.1wt%-5wt% can effectively improve the cycle stability of the cathode material while reducing material costs.
[0042] In some embodiments, the tap density (TD) of the cathode material precursor is 0.5 g / cm³. 3 -1.8 g / cm 3 For example, it can be 0.50 g / cm 3 0.55 g / cm 3 0.60 g / cm 3 0.65 g / cm 3 0.70 g / cm 3 0.75 g / cm 3 0.80 g / cm 3 0.85 g / cm 3 0.90 g / cm 3 0.95 g / cm 3 1.00 g / cm 3 1.05 g / cm 3 1.10 g / cm 3 1.15 g / cm 3 1.20 g / cm 3 1.25 g / cm3 1.30 g / cm 3 1.35 g / cm 3 1.40 g / cm 3 1.45 g / cm 3 1.50 g / cm 3 1.55 g / cm 3 1.60 g / cm 3 1.65 g / cm 3 1.70 g / cm 3 1.75 g / cm 3 1.80 g / cm 3 or 0.5 g / cm 3 -1.8 g / cm 3 Any value within the range. Within this range, the tap density TD indicates a high compaction density of the cathode material after sintering, which is beneficial for improving the volumetric energy density of the battery. If the tap density TD of the cathode material precursor is too low, the compaction density of the cathode material will be insufficient, leading to a decrease in volumetric energy density. If the tap density TD is too high, it may result in insufficient porosity of the cathode material, affecting electrolyte wetting and ion transport.
[0043] In some embodiments, the specific surface area (BET) of the cathode material precursor is 15 m². 2 / g -40 m 2 / g, for example, the specific surface area BET of the cathode material precursor can be 15 m² / g. 2 / g、16 m 2 / g、17 m 2 / g、18 m 2 / g、19 m 2 / g、20 m 2 / g、21 m 2 / g、22 m 2 / g、23 m 2 / g、24 m 2 / g、25 m 2 / g、26 m 2 / g、27 m 2 / g、28 m 2 / g、29 m 2 / g、30 m 2 / g、31 m 2 / g、32 m 2 / g、33 m 2 / g、34 m 2 / g、35 m 2 / g、36 m 2 / g、37 m 2 / g、38 m 2 / g、39 m 2 / g、40 m 2 / g or 15m 2 / g-40 m 2 Any value within the range of / g. If the specific surface area (BET) of the cathode material precursor is too small, the reactivity of the cathode material will be insufficient. If the specific surface area (BET) of the cathode material precursor is too large, the surface side reactions will be aggravated during charge-discharge cycling, which is not conducive to improving cycle performance. The specific surface area (BET) of the cathode material precursor is within 15 m². 2 / g -40 m 2 Within the range of / g, the sintered cathode material has a suitable number of active sites and electrolyte contact area, taking into account both reactivity and surface stability, so as to achieve a balance between cycle performance and rate performance.
[0044] In some embodiments, the particle size distribution K90 of the cathode material precursor is 0.6-1.0. Exemplarily, the particle size distribution of the cathode material precursor can be any value within the range of 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 1.00, or 0.6-1.0. A particle size distribution K90 within this range indicates a narrower particle size distribution, suggesting good uniformity of primary particle size. This is beneficial for reducing stress concentration and structural deterioration during the charge-discharge process of the cathode material after sintering, and improving cycle stability.
[0045] In some embodiments, the molar amount of Ni accounts for 0.10-0.25 of the total molar amount of metal in the cathode material precursor. Optionally, the molar amount of Ni accounts for 0.15-0.25 of the total molar amount of metal in the cathode material precursor; alternatively, the molar amount of Ni accounts for 0.20-0.25 of the total molar amount of metal in the cathode material precursor. Exemplarily, the molar amount of Ni in the total molar amount of metal in the cathode material precursor can be any value among >0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, <0.25, or less than 0.25 but greater than 0.10. Having the molar amount of Ni in the total molar amount of metal in the cathode material precursor within this range allows the sintered cathode material to maintain a spinel structure while reducing material costs.
[0046] In some embodiments, the molar amount of Mn element accounts for 0.70-0.80% of the total molar amount of metal in the cathode material precursor. Exemplarily, the molar amount of Mn element in the total molar amount of metal in the cathode material precursor can be any value within the range of >0.70, 0.72, 0.74, 0.75, 0.76, 0.78, <0.80, or below 0.80 but above 0.70. Having the molar amount of Mn element within this range is beneficial for reducing costs and improving structural stability under high voltage.
[0047] In some embodiments, the cathode material precursor also contains the metallic element Co, with the molar amount of Co accounting for less than 0.05 of the total molar amount of metal in the cathode material precursor. For example, the molar amount of Co can be any value within the range of 0, 0.01, 0.02, 0.03, 0.04, 0.05, or 0-0.05. The introduction of Co can stabilize the material structure and suppress phase transitions during cycling.
[0048] In some embodiments, the chemical formula of the cathode material precursor is: Ni x Co y Mn z Al a T b (OH) 2+δ , Wherein, 0.10≤x≤0.25, 0≤y≤0.05, 0.70≤z≤0.80, 0.010≤a≤0.147, 0≤b≤0.01, 0.01<δ≤0.19, x+y+z+a+b=1, and the doped metal element T is at least one of W, Y, Mo, Nb, Zr, Ti, and Sb.
[0049] In the above chemical formulas, x represents the ratio of the molar amount of Ni to the total molar amount of the metallic elements, and the range of x is 0.10 ≤ x ≤ 0.25. For example, x can be any value within the range of 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, or 0.10-0.25. y represents the ratio of the molar amount of Co to the total molar amount of the metallic elements, and the range of y is 0 ≤ y ≤ 0.05. For example, y can be any value within the range of 0, 0.01, 0.02, 0.03, 0.04, 0.05, or 0-0.05. z represents the ratio of the molar amount of Mn to the total molar amount of metallic elements. The range of z is 0.70 ≤ z ≤ 0.80. For example, z can be any value in the range of 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, or 0.70-0.80. 'a' represents the ratio of the molar amount of Al to the total molar amount of all metallic elements. The range of 'a' is 0.010 ≤ a ≤ 0.147. For example, 'a' can be any value within the range of 0.010, 0.020, 0.030, 0.040, 0.050, 0.060, 0.070, 0.080, 0.090, 0.100, 0.110, 0.120, 0.130, 0.140, 0.147, or 0.010-0.147. b represents the ratio of the molar amount of doped metal element T to the molar amount of total metal elements. The range of b is 0 ≤ b ≤ 0.01. For example, b can be any value in the range of 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010 or 0-0.01. δ represents the non-stoichiometric coefficient of oxygen, which represents the balanced charge of oxygen when the valence of dopant element T is higher than 2. The range of δ is 0.01≤δ≤0.19. For example, δ can be any value in the range of 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19 or 0.01-0.19.
[0050] By controlling the molar ratio of nickel, manganese, and aluminum in the cathode material precursor within a specific range, and calcining it to obtain a spinel-type cathode material, the material can be used at a high voltage of 4.7V to avoid the formation of Mn. 3+ The Jahn-Teller distortion and dissociation induced by this process maintain the stability of the crystal structure and significantly improve cycle life.
[0051] It should be understood that the cathode material precursor in the embodiments of this application also has a hydroxide of Co element and / or dopant element T. By appropriately doping, the performance of a certain aspect of the cathode material can be enhanced, thereby improving the electrochemical performance of the battery.
[0052] To prepare the aforementioned cathode material precursor, another embodiment of this application provides a method for preparing the cathode material precursor based on a co-precipitation method. The preparation method specifically described in this embodiment is merely one exemplary and non-limiting implementation of this application. Any other method capable of preparing a cathode material precursor having the composition, structure, and properties of this application should be considered to fall within the scope of protection sought by this application based on the cathode material precursor product itself.
[0053] This application provides a method for preparing a cathode material precursor, including: A co-precipitation reaction is carried out by passing a metal salt solution containing Ni, Mn and Al elements, a complexing agent solution and a precipitant solution into a bottom liquid containing a precipitant and a complexing agent to obtain a hydroxide slurry with the target particle size. The hydroxide slurry was post-processed to obtain the cathode material precursor.
[0054] In some embodiments, the metal salt of the metal salt solution includes one or more of sulfates, nitrates, or chlorides containing Ni, Mn, or Al elements; optionally, the metal salt of the metal salt solution also includes one or more of sulfates, nitrates, or chlorides doped with metal element T.
[0055] In some embodiments, the precipitant includes one or more of sodium carbonate, sodium hydroxide, or potassium hydroxide.
[0056] In some embodiments, the complexing agent includes one or more of ammonia, oxalic acid, and ethylenediaminetetraacetic acid.
[0057] In some embodiments, the total mass concentration of the metal salt in the metal salt solution is 100 g / L-150 g / L. Exemplarily, the total mass concentration of the metal salt in the metal salt solution can be any value within the range of 100 g / L, 120 g / L, 150 g / L, or 100 g / L-150 g / L. If the total mass concentration of the metal salt in the metal salt solution is too low, the reaction rate is slow and the production efficiency is low. Conversely, if the total mass concentration of the metal salt in the metal salt solution is too high, the reaction is too fast, which can easily lead to particle agglomeration and Al element segregation.
[0058] In some embodiments, the solute mass fraction of the precipitant solution is 30wt%-70wt%. Exemplarily, the solute mass fraction of the precipitant solution can be any value within the range of 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, or 30wt%-70wt%.
[0059] In some embodiments, the solute mass fraction of the complexing agent solution is 10wt%-30wt%. Exemplarily, the solute mass fraction of the complexing agent solution can be any value within the range of 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, or 10wt%-30wt%.
[0060] In some embodiments, the pH of the substrate is 10.5-12.0. Exemplarily, the pH of the substrate can be any value within the range of 10.5, 10.6, 10.7, 10.8, 10.9, 11.0, 11.2, 11.4, 11.5, 11.6, 11.7, 11.8, 11.9, 12.0, or 10.5-12.0. If the pH of the substrate is too high, the co-precipitation reaction will be too rapid, easily leading to primary particle agglomeration and Al segregation during precipitation. Within this pH range, Ni... 2+ Mn 2+ Al 3+ The precipitation rates tend to be synchronized, which is beneficial for achieving co-precipitation and uniform distribution of Al.
[0061] In some embodiments, the complexing agent concentration of the substrate solution is 1.5 g / L-3 g / L. Exemplarily, the complexing agent concentration of the substrate solution can be any value within the range of 1.5 g / L, 1.75 g / L, 2.0 g / L, 2.25 g / L, 2.5 g / L, 2.75 g / L, 3.0 g / L, or 1.5 g / L-3.0 g / L. The complexing agent concentration of the substrate solution affects the initial nucleation environment and the growth habit of primary particles. If the complexing agent concentration of the substrate solution is too low, the complexation buffering capacity is insufficient, and the initial primary particles grow too quickly; if the complexing agent concentration of the substrate solution is too high, the initial precipitation is excessively inhibited, prolonging the reaction time.
[0062] In some embodiments, the coprecipitation reaction is carried out under stirring at a speed of 300 rpm to 900 rpm. For example, the stirring speed can be any value within the range of 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm or 300 rpm to 900 rpm.
[0063] In some embodiments, the pH value during the coprecipitation reaction is controlled to decrease from 10.5-12.0 to 9.0-10.0; exemplaryly, the pH value can decrease from 10.5 to 9.0, 10.8 to 9.0, 11.0 to 9.0, 11.3 to 9.0, 11.5 to 9.0, 11.8 to 9.0, 12.0 to 9.0, 10.5 to 9.3, 10.8 to 9.3, 11.0 to 9.3, 11.3 to 9.3, 11.5 to 9.3, 11.8 to 9.3, 12.0 to 9.3, 10.5 to 9.5, 10.8 to 9.5, 11.0 to 9.5, 1... 1.3 decreased to 9.5, 11.5 decreased to 9.5, 11.8 decreased to 9.5, 12.0 decreased to 9.5, 10.5 decreased to 9.8, 10.8 decreased to 9.8, 11.0 decreased to 9.8, 11.3 decreased to 9.8, 11.5 decreased to 9.8, 11.8 decreased to 9.8, 12.0 decreased to 9.8, 10.5 decreased to 10.0, 10.8 decreased to 10.0, 11.0 decreased to 10.0, 11.3 decreased to 10.0, 11.5 decreased to 10.0, 11.8 decreased to 10.0, 12.0 decreased to 10.0, or any pH value within the range of 10.5-12.0 decreased to any pH value within the range of 9.0-10.0.
[0064] In some embodiments, the concentration of the complexing agent during the co-precipitation reaction is controlled to decrease from 1.5 g / L-3 g / L to <1.5 g / L; exemplaryly, the concentration of the complexing agent can decrease from 1.5 g / L to 1.4 g / L, 1.8 g / L to 1.4 g / L, 2.0 g / L to 1.4 g / L, 2.3 g / L to 1.4 g / L, 2.5 g / L to 1.4 g / L, 2.8 g / L to 1.4 g / L, 3 g / L to 1.4 g / L, from 1.5 g / L to 1.2 g / L, and 1.8 g / L to 1.8 g / L. / L decreased to 1.2g / L, 2.0g / L decreased to 1.2g / L, 2.3g / L decreased to 1.2g / L, 2.5g / L decreased to 1.2g / L, 2.8g / L decreased to 1.2g / L, 3g / L decreased to 1.2g / L, from 1.5g / L to 1g / L, 1.8g / L decreased to 1g / L, 2.0g / L decreased to 1g / L, 2.3g / L decreased to 1g / L, 2.5g / L decreased to 1g / L, 2.8g / L decreased to 1g / L, 3g / L decreased to 1g / L, from 1. The concentration decreased from 5 g / L to 0.8 g / L, 1.8 g / L to 0.8 g / L, 2.0 g / L to 0.8 g / L, 2.3 g / L to 0.8 g / L, 2.5 g / L to 0.8 g / L, 2.8 g / L to 0.8 g / L, 3 g / L to 0.8 g / L, from 1.5 g / L to 0.5 g / L, 1.8 g / L to 0.5 g / L, 2.0 g / L to 0.5 g / L, 2.3 g / L to 0.5 g / L, 2.5 g / L to 0.5 g / L, 2... The concentration of any complexing agent decreases from 0.8 g / L to 0.5 g / L, from 3 g / L to 0.5 g / L, from 1.5 g / L to 0.1 g / L, from 1.8 g / L to 0.1 g / L, from 2.0 g / L to 0.1 g / L, from 2.3 g / L to 0.1 g / L, from 2.5 g / L to 0.1 g / L, from 2.8 g / L to 0.1 g / L, from 3 g / L to 0.1 g / L, or any complexing agent concentration within the range of 1.5 g / L to 3 g / L decreases to less than 1.5 g / L and greater than 0.
[0065] By controlling the concentrations of the metal salt solution, complexing agent solution, and precipitant solution, as well as the flow rate ratio of these solutions, the pH value and complexing agent concentration during the co-precipitation reaction can be controlled, thereby controlling the sedimentation rate and uniformity of each metal. By precisely controlling the flow rate ratio of these three components, a balance between the precipitation rate and the complexation rate can be achieved, resulting in cathode material precursor particles with uniform particle size and dense structure.
[0066] In some embodiments, during the co-precipitation reaction, the mother liquor is discharged through a concentration device, and the discharge rate of the mother liquor is consistent with the total inflow rate. This helps to maintain a constant solid content and volume of the slurry in the reactor, avoids excessive dilution or concentration of the reaction system, and allows the primary particles to grow in a constant chemical environment, which is beneficial for obtaining cathode material precursor particles with uniform particle size and dense structure.
[0067] It should be understood that during the co-precipitation reaction, process parameters such as the pH value and complexing agent concentration of the underlying solution, the stirring speed, the flow rate of the metal salt, and the flow rate ratio of the metal salt solution, complexing agent solution, and precipitant solution all jointly affect the nucleation, growth, and aggregation behavior of primary particles, thereby determining the particle size, morphology, and density of secondary particles. By optimizing these parameters, simultaneous co-precipitation of Al with Ni and Mn can be achieved, ensuring uniform Al distribution while obtaining small particle sizes (D50 = 3-6 μm) and higher tap density (TD = k × φ) compared to other products at the same level of high aluminum doping. -0.393 Where k is 0.6229 g / cm³ 3 -0.9526g / cm 3 φ is the mass fraction of Al in the cathode material precursor (×100).
[0068] In some embodiments, the post-processing includes sequential dehydration, washing, and drying. For example, a centrifuge is used to dehydrate and wash the hydroxide slurry, followed by oven drying to obtain the cathode material precursor.
[0069] Some embodiments of this application provide a cathode material, which is prepared by calcining a cathode material precursor as described in any of the above embodiments or by mixing the above cathode material precursor with lithium. For example, a cathode material precursor is mixed with lithium hydroxide, and then the lithium-mixed material is calcined in oxygen to form a cathode material.
[0070] Some embodiments of this application provide a battery, wherein the positive electrode of the battery is made of the positive electrode material described in the above embodiments.
[0071] Some embodiments of this application provide an electrical device, including a battery as described in the above embodiments.
[0072] The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all reagents and raw materials used in the embodiments are commercially available or synthesized by conventional methods, and the instruments used in the embodiments are also commercially available.
[0073] The test methods for the cathode material precursors involved in this application are as follows: D10, D50, and D90 were measured using a laser particle size analyzer (Mastersizer 3000) in accordance with the national standard GB / T 19077-2016 Particle Size Analysis by Laser Diffraction. Wherein, D10 is the particle size corresponding to a cumulative volume fraction of 10% in the particle size distribution, D50 is the particle size corresponding to a cumulative volume fraction of 50% in the particle size distribution, and D90 is the particle size corresponding to a cumulative volume fraction of 90% in the particle size distribution. The formula for calculating K90 of particle size distribution is: K90 = (D90 - D10) / D50.
[0074] BET (Specific Surface Area): Measured using a fully automated nitrogen adsorption specific surface area analyzer (instrument model: BELPREP-VACII / BELSORP-MINI-X), in accordance with the national standard GB / T 19587-2017 "Determination of Specific Surface Area of Solid Substances by Gas Adsorption BET Method".
[0075] TD (Tap Density): Measured using a powder tap density tester (model: Dandong Baite BT-302) in accordance with the national standard GB / T 5162-2021 "Determination of Tap Density of Metal Powders".
[0076] The total content of nickel, cobalt, manganese, al, and other doping elements (T) was determined by inductively coupled plasma mass spectrometry (ICP-MS) (Agilent 7850 ICP-MS), in accordance with the national standard GB / T 8647.11-2019 Nickel Chemical Analysis Methods Part 11: Determination of the Content of Magnesium, Aluminum, Manganese, Cobalt, Copper, Zinc, Cadmium, Tin, Antimony, Lead and Bismuth by Inductively Coupled Plasma Mass Spectrometry.
[0077] The relative standard deviation (RSD) of the Al content distribution was determined by cutting secondary particles of the cathode material using ion milling. Multiple cut secondary particles were obtained, and a single particle with a complete cross-section was randomly selected. Line or surface scanning was then performed on the entire cross-section of the secondary particle and its adjacent areas to obtain the Al content distribution data. The data was then processed. The specific data processing steps are as follows: ① Data filtering range: Line scan data filters data within a straight line area that runs radially through the geometric center of the secondary particle cross-section and extends 0.8 times the radius of the secondary particle (0.8r) to both sides from the geometric center; area scan data filters data within a circular area centered on the geometric center of the secondary particle cross-section and within 0.8 times the radius of the secondary particle (0.8r).
[0078] ② Select data: After determining the data range, you can select all, randomly, or according to a certain pattern (such as scanning data at certain intervals) and put the data into the dataset.
[0079] ③ Calculate the relative standard deviation (RSD) of the mass content distribution of Al element. The calculation formula is: ; In the formula, RSD is the relative standard deviation of the mass content distribution of Al element; SD is the standard deviation of the mass content distribution of Al element; This represents the average mass content of Al element; N is the number of samples containing the mass content of Al element; i is the sample number, i = 1, 2, ..., N; xi is the mass content detection value of the i-th Al element.
[0080] Example 1 A cathode material precursor is provided, and its preparation method is as follows: (1) Prepare the solution: Weigh battery-grade nickel sulfate, manganese sulfate and aluminum sulfate according to the molar ratio of Ni:Mn:Al=24:75:1, add water to prepare a metal salt solution with a total mass concentration of 120g / L; prepare a sodium hydroxide solution with a solute mass fraction of 62.5wt% and an ammonia solution with a solute mass fraction of 20.5wt%.
[0081] (2) Product preparation: Pure water, sodium hydroxide solution and ammonia water are added to the reactor to prepare the base solution. The pH value of the base solution is 11.0 and the concentration of ammonia water is 1.5 g / L. Nitrogen gas is introduced as a protective gas. Then, metal salt solution, sodium hydroxide solution and ammonia water are introduced into the base solution in parallel and then into the reactor for co-precipitation reaction. During the co-precipitation reaction, the pH value is controlled to decrease from 11.0 to 9.5, the concentration of ammonia water is controlled to decrease from 1.5 g / L to 1.0 g / L, the flow rate of metal salt solution is 5% / h of reactor volume, the reaction temperature is 60℃, the stirring speed is 700 rpm, and the mother liquor is discharged through the concentration equipment during the reaction. The discharge rate of the mother liquor is consistent with the total inflow rate until a slurry with a target particle size of about 4.5 μm is obtained. The hydroxide slurry is dehydrated and washed using a centrifuge, and then dried at 120℃ for 12 h to obtain the cathode material precursor.
[0082] The surface SEM image of the secondary particles of the cathode material precursor prepared in Example 1 is shown below. Figure 1 As shown.
[0083] Example 2 A cathode material precursor is provided, the preparation method of which differs from that of Example 1 in that: (1) Prepare the solution: Weigh battery-grade nickel sulfate, manganese sulfate and aluminum sulfate according to the molar ratio of Ni:Mn:Al=21.7:75:3.3, and add water to prepare a metal salt solution with a total mass concentration of 120g / L.
[0084] (2) Product preparation: Control the ammonia concentration to decrease from 1.5 g / L to 0.8 g / L during the co-precipitation reaction.
[0085] Example 3 A cathode material precursor is provided, the preparation method of which differs from that of Example 1 in that: (1) Prepare the solution: Weigh battery-grade nickel sulfate, manganese sulfate and aluminum sulfate according to the molar ratio of Ni:Mn:Al=20:75:5, and add water to prepare a metal salt solution with a total mass concentration of 120g / L.
[0086] (2) Product preparation: During the co-precipitation reaction, the concentration of ammonia water was reduced from 1.5 g / L to 0.6 g / L.
[0087] Example 4 A cathode material precursor is provided, the preparation method of which differs from that of Example 1 in that: (1) Prepare the solution: Weigh battery-grade nickel sulfate, cobalt sulfate, manganese sulfate and aluminum sulfate according to the molar ratio of Ni:Co:Mn:Al:=14:1:75:10, and add water to prepare a metal salt solution with a total mass concentration of 120g / L.
[0088] Example 5 A cathode material precursor is provided, the preparation method of which differs from that of Example 1 in that: (1) Prepare the solution: Weigh battery-grade nickel sulfate, manganese sulfate and aluminum sulfate according to the molar ratio of Ni:Mn:Al=21.7:75:3.3, and add water to prepare a metal salt solution with a total mass concentration of 120g / L.
[0089] (2) Product preparation: During the co-precipitation reaction, the concentration of ammonia water was reduced from 1.5 g / L to 0.1 g / L.
[0090] Comparative Example 1 A cathode material precursor is provided, the preparation method of which differs from that of Example 1 in that: (1) Prepare the solution: Weigh battery-grade nickel sulfate, manganese sulfate and aluminum sulfate according to the molar ratio of Ni:Mn:Al=21.7:75:3.3, and add water to prepare a metal salt solution with a total mass concentration of 120g / L.
[0091] (2) Product preparation: The pH value of the base liquid is 10.8; during the co-precipitation reaction, the pH value is reduced from 10.8 to 9.5 and the ammonia concentration is reduced from 1.5 g / L to 0.4 g / L until a slurry with a target particle size of about 7 μm is obtained.
[0092] Comparative Example 2 A cathode material precursor is provided, the preparation method of which differs from that of Example 1 in that: (1) Prepare the solution: Weigh battery-grade nickel sulfate, manganese sulfate and aluminum sulfate according to the molar ratio of Ni:Mn:Al=21.7:75:3.3, and add water to prepare a metal salt solution with a total mass concentration of 120g / L.
[0093] (2) Product preparation: The pH value of the base liquid is 11.6; during the co-precipitation reaction, the pH value is reduced from 11.6 to 9.5, the ammonia concentration is reduced from 1.5 g / L to 0.4 g / L, and the stirring speed is 900 rpm until a slurry with a target particle size of about 2.5 μm is obtained.
[0094] Comparative Example 3 A cathode material precursor is provided, the preparation method of which differs from that of Example 1 in that: (1) Prepare the solution: Weigh battery-grade nickel sulfate, manganese sulfate and aluminum sulfate according to the molar ratio of Ni:Mn:Al=21.7:75:3.3, and add water to prepare a metal salt solution with a total mass concentration of 120g / L.
[0095] (2) Product preparation: The pH value of the base liquid is 10.6; during the co-precipitation reaction, the pH value is reduced from 10.6 to 9.5, and the ammonia concentration is reduced from 1.5 g / L to 0.4 g / L until a slurry with a target particle size of about 10 μm is obtained.
[0096] Comparative Example 4 A cathode material precursor is provided, the preparation method of which differs from that of Example 1 in that: (1) Prepare the solution: Weigh battery-grade nickel sulfate, manganese sulfate and aluminum sulfate according to the molar ratio of Ni:Mn:Al=21.7:75:3.3, and add water to prepare a metal salt solution with a total mass concentration of 120g / L.
[0097] (2) Product preparation: The pH value of the base liquid is 11.8; during the co-precipitation reaction, the pH value is reduced from 11.8 to 9.5, the ammonia concentration is reduced from 1.5 g / L to 0.4 g / L, and the stirring speed is 900 rpm until a slurry with a target particle size of about 1.5 μm is obtained.
[0098] Comparative Example 5 A cathode material precursor is provided, the preparation method of which differs from that of Example 1 in that: (1) Prepare the solution: Weigh battery-grade nickel sulfate, manganese sulfate and aluminum sulfate according to the molar ratio of Ni:Mn:Al=65:31.7:3.3, and add water to prepare a metal salt solution with a total mass concentration of 120g / L.
[0099] (2) Product preparation: The ammonia concentration of the base solution is 3.0 g / L; during the co-precipitation reaction, the ammonia concentration is reduced from 3.0 g / L to 1.5 g / L.
[0100] Comparative Example 6 A cathode material precursor is provided, the preparation method of which differs from that of Example 1 in that: (1) Prepare the solution: Weigh battery-grade nickel sulfate, iron sulfate, manganese sulfate and aluminum sulfate according to the molar ratio of Ni:Fe:Mn:Al=20:1.7:75:3.3, and add water to prepare a metal salt solution with a total mass concentration of 120g / L.
[0101] (2) Product preparation: During the co-precipitation reaction, the concentration of ammonia water was reduced from 1.5 g / L to 0.4 g / L.
[0102] Comparative Example 7 A cathode material precursor is provided, the preparation method of which differs from that of Example 1 in that: (1) Prepare the solution: Weigh battery-grade nickel sulfate, manganese sulfate and aluminum sulfate according to the molar ratio of Ni:Mn:Al=10:75:15, and add water to prepare a metal salt solution with a total mass concentration of 120g / L.
[0103] (2) Product preparation: The ammonia concentration of the base solution is 3.0 g / L; during the co-precipitation reaction, the pH value is 10.8-11.2 and the ammonia concentration is 2.5 g / L-3.5 g / L.
[0104] Comparative Example 8 A cathode material precursor is provided, the preparation method of which differs from that of Example 1 in that: (1) Prepare the solution: Weigh battery-grade nickel sulfate, manganese sulfate and aluminum sulfate according to the molar ratio of Ni:Mn:Al=24.8:75:0.2, and add water to prepare a metal salt solution with a total mass concentration of 120g / L.
[0105] Comparative Example 9 A cathode material precursor is provided, the preparation method of which differs from that of Example 1 in that: (1) Prepare the solution: Weigh battery-grade nickel sulfate and manganese sulfate according to the molar ratio of Ni:Mn=25:75, and add water to prepare a metal salt solution with a total mass concentration of 120g / L.
[0106] Physicochemical analysis Table 1. Statistical Table of Physicochemical Data of Cathode Material Precursor Note 1: Test TD is the tap density obtained from actual testing; 2. The lower limit of TD is calculated using the formula TD=k×φ -0.393 Where k is 0.6229 g / cm³ 3 The calculated tap data; 3. The lower limit of TD is calculated using the formula TD=k×φ -0.393 Where k is 0.9526 g / cm³ 3 The calculated vibration data.
[0107] Table 2. Statistical Table of Physicochemical Data of Cathode Material Precursor To verify the performance advantages of the cathode material precursors prepared in each embodiment and comparative example, cathode materials were prepared using the cathode material precursors prepared in each embodiment and comparative example. The preparation process of each cathode material is as follows: Cathode sintering: The cathode material precursors prepared in each example and comparative example were mixed with lithium hydroxide at a total metal element to lithium molar ratio of 1:0.5 and calcined in a muffle furnace at a heating rate of 3℃ / min to 900℃ for 15 hours. After cooling, they were crushed and sieved to obtain the cathode material.
[0108] Furthermore, the cathode materials prepared from the cathode material precursors of each embodiment and comparative example were used to assemble pouch cells for electrochemical performance testing. The cell preparation and testing process is as follows: ① Button test The lithium nickel manganese oxide cathode materials obtained from the above embodiments and comparative examples were mixed with conductive acetylene black and binder polyvinylidene fluoride (PVDF) (prepared as an 8 wt% PVDF / NMP solution) at a mass ratio of 8:1:1. The mixture was coated on aluminum foil to form a cathode sheet. The anode sheet was a lithium metal sheet. The electrolyte was 1 mol / L LiPF6 / EC:DMC (volume ratio 1:1), with 5 wt% fluoroethylene carbonate (FEC) added as a high-voltage additive. The battery casing, positive and negative electrode sheets, separator (Celgard-2325), spring sheet, gasket, and electrolyte were assembled into a CR-2032 type half cell in a vacuum glove box.
[0109] Electrochemical performance tests were conducted on each CR-2032 half-cell using the Blue Electric testing system. Specifically, charge-discharge tests were performed at room temperature with a voltage window of 3.5-4.95 V. The discharge specific capacity at 0.1C and 3C currents was tested, as well as the capacity retention rate after 100 cycles at 2C current, with 1C = 147 mAh / g.
[0110] ② Full electrical test The lithium nickel manganese oxide cathode materials obtained from the precursor preparations of the lithium nickel manganese oxide cathode materials in the above embodiments and comparative examples were mixed with conductive acetylene black and binder polyvinylidene fluoride (PVDF) (prepared as an 8 wt% PVDF / NMP solution) at a mass ratio of 8:1:1, and coated onto aluminum foil to form a cathode sheet. A graphite cathode sheet was used as the anode (or a mixture of graphite, conductive carbon black, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) at a mass ratio of 92:2:3:3 was coated onto copper foil to form a cathode sheet). Using Celgard-2325 as the separator and 1 mol / L LiPF6 / EC:DMC (volume ratio 1:1) as the electrolyte, with 5 wt% fluoroethylene carbonate (FEC) added as a high-voltage additive, a CR-2032 type full cell was assembled in a vacuum glove box.
[0111] The electrochemical performance of the full cell was tested using the Blue Electricity testing system, specifically including: Room temperature cycling performance: At room temperature (25℃), charge and discharge cycle tests were conducted at 1C current within a voltage window of 3.4-4.85 V, and the number of cycles when the capacity retention rate was 80% was recorded. High-temperature cycling performance: Under high temperature (45℃) conditions, charge-discharge cycle tests were conducted at 1C current within a voltage window of 3.4-4.85 V, and the number of cycles when the capacity retention rate was 80% was recorded.
[0112] Wherein, 1C = 147 mA / g. The statistical results of the tests are shown in Table 3 below: The test results are summarized in Table 3 below: Table 3. Statistical Table of Electrochemical Data for Cathode Materials Performance Analysis: Examples 1-5 of this application provide a cathode material precursor, which is a hydroxide containing the metal elements Ni, Mn, and Al. The molar amount of Mn accounts for more than 0.5% of the total molar amount of the cathode material precursor, and the molar amount of Al accounts for 0.010-0.147% of the total molar amount of the cathode material precursor. The average particle size D50 of the cathode material precursor is 3μm-6μm. The tap density TD of the cathode material precursor satisfies the following relationship: TD=k×φ -0.393Where k is 0.6229 g / cm³ 3 -0.9526g / cm 3 φ represents the mass fraction of Al in the cathode material precursor × 100. The cathode material precursor provided in this application is beneficial for achieving an effective balance between excellent rate performance at high voltage and long-cycle stability of the battery.
[0113] The technical features described above can be combined arbitrarily. Although not all possible combinations of these technical features are described, any combination of these technical features should be considered to be covered by this specification, provided that such combination does not contain contradictions.
[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A cathode material precursor, characterized in that, The cathode material precursor is a hydroxide containing the metal elements Ni, Mn and Al, wherein the molar amount of Mn accounts for more than 0.5% of the total molar amount of the cathode material precursor, and the molar amount of Al accounts for 0.010-0.147% of the total molar amount of the cathode material precursor. The average particle size D50 of the cathode material precursor is 3μm-6μm; The tap density TD of the cathode material precursor satisfies the following relationship: TD=k×φ -0.393 The unit of TD is g / cm³. 3 k is 0.6229 g / cm³ 3 -0.9526g / cm 3 φ is the mass fraction of Al in the cathode material precursor × 100.
2. The cathode material precursor according to claim 1, characterized in that, In the cathode material precursor, the relative standard deviation (RSD) of the mass content distribution of the Al element is less than 20%; optionally, the relative standard deviation (RSD) of the mass content distribution of the Al element is less than 10%.
3. The cathode material precursor according to claim 1, characterized in that, At least one of the following conditions must be met: A. The mass fraction of Al element in the cathode material precursor is 0.1wt%-5wt%; B. The tap density TD of the cathode material precursor is 0.5 g / cm³. 3 -1.8 g / cm 3 ; C. The specific surface area (BET) of the cathode material precursor is 15 m². 2 / g -40 m 2 / g; D. The particle size distribution K90 of the cathode material precursor is 0.6-1.0; E. The molar amount of Ni element accounts for 0.10-0.25% of the total molar amount of metal in the cathode material precursor; F. The molar amount of the Mn element accounts for 0.70-0.80% of the total molar amount of metal in the cathode material precursor; G. The cathode material precursor also contains the metallic element Co, and the molar amount of Co accounts for less than 0.05% of the total molar amount of metals in the cathode material precursor.
4. The cathode material precursor according to any one of claims 1 to 3, characterized in that, The chemical formula of the cathode material precursor is: Ni x What y Mn z Al a T b (OH) 2+δ , Wherein, 0.10≤x≤0.25, 0≤y≤0.05, 0.70≤z≤0.80, 0.010≤a≤0.147, 0≤b≤0.01, 0.01≤δ≤0.19, x+y+z+a+b=1, and the doped metal element T is at least one of W, Y, Mo, Nb, Zr, Ti, and Sb.
5. A method for preparing a cathode material precursor as described in any one of claims 1 to 4, characterized in that, include: A co-precipitation reaction is carried out by passing a metal salt solution containing Ni, Mn and Al elements, a complexing agent solution and a precipitant solution into a bottom liquid containing a precipitant and a complexing agent to obtain a hydroxide slurry with the target particle size. The hydroxide slurry is post-processed to obtain a cathode material precursor.
6. The method for preparing the cathode material precursor according to claim 5, characterized in that, The preparation method satisfies at least one of the following conditions: (1) The metal salt of the metal salt solution includes one or more of sulfate, nitrate or chloride containing Ni, Mn or Al elements; optionally, the metal salt of the metal salt solution also includes one or more of sulfate, nitrate or chloride doped with metal element T. (2) The precipitant includes one or more of sodium carbonate, sodium hydroxide, or potassium hydroxide; (3) The complexing agent includes one or more of ammonia, oxalic acid, and ethylenediaminetetraacetic acid; (4) The total mass concentration of the metal salt in the metal salt solution is 100 g / L-150 g / L; (5) The mass fraction of the solute in the precipitant solution is 30wt%-70wt%; (6) The solute mass fraction of the complexing agent solution is 10wt%-30wt%; (7) The pH of the substrate solution is 10.5-12.0; (8) The concentration of the complexing agent in the base liquid is 1.5 g / L-3 g / L.
7. The method for preparing the cathode material precursor according to claim 5, characterized in that, The preparation method satisfies at least one of the following conditions: (9) The coprecipitation reaction is carried out under stirring at a speed of 300 rpm to 900 rpm; (10) During the coprecipitation reaction, the flow rate of the metal salt solution is controlled to be 1% / h - 15% / h of the reaction vessel volume; (11) Control the pH value during the coprecipitation reaction process to decrease from 10.5-12.0 to 9.0-10.0; (12) Control the concentration of the complexing agent in the coprecipitation reaction process to decrease from 1.5 g / L-3 g / L to <1.5 g / L; (13) During the co-precipitation reaction, the mother liquor is discharged through a concentration device, and the discharge rate of the mother liquor is consistent with the total inflow rate; (14) The post-processing includes dehydration, washing and drying processes performed sequentially.
8. A positive electrode material, characterized in that, The cathode material is prepared by lithium mixing and calcining the cathode material precursor as described in any one of claims 1-4 or the cathode material precursor obtained by the preparation method described in any one of claims 5-7.
9. A battery, characterized in that, The positive electrode of the battery is made of the positive electrode material as described in claim 8.
10. An electrical-related device, characterized in that, Includes the battery as described in claim 9.